Pediatric palliative care: Global perspectives - Madden, Vanessa; Fowler-Kerry, Susan; Knapp, Caprice (Springer Netherlands, 2012)
The first of its kind, this book describes pediatric palliative care in more than 23 countries. Each region in the world is covered and countries included are both resource poor and rich. Authors are multidisciplinary and regarded nationally and internationally in their field. Clinicians, advocates, policymakers, funders, and researchers will learn how programs were developed and implemented in each country. Authors describe children for whom pediatric palliative care is needed and provided for in their country. When applicable, a brief history of pediatric palliative care is included noting especially policy changes and legislative acts. For example, the chapter on Poland describes how pediatric palliative care grew from the Catholic church into a national movement spearheaded by several health care workers. The Pole national spirit that brought them through a change in political regime has also been a driving force in the pediatric palliative care movement. The chapter on South Africa, for example, illustrates how a resource poor country has been able to leverage philanthropic and government funding to make its dream of having an infrastructure of pediatric palliative care a reality. These are just a few examples of the inspiring stories that are included in this book. Readers from countries who wish to start a pediatric palliative care program, or advance an existing program, will learn valuable lessons from others who have faced similar barriers. Introduction and concluding chapters highlight the strengths and weaknesses of the modern pediatric palliative care movement.